The Influence of Brand Image, Service Quality, and Product Quality on Customer Repurchase Intention Mediating to Customer Satisfaction Towards KFC Restaurant in Pontianak - admin, ESTER KRISTIANTI B12112013 (Jurnal Manajemen Update, 2016)
The increase of competitive environment in food industry sector, especially fast food industry drives fast food industry to have more consideration on customer satisfaction to win the competition. Some elements that cannot be separated from fast food industry are brand image, food quality,and service quality. The study aimed to figure out the influence of brand image, product quality, and service quality toward customer repurchase intention mediating to customer satisfaction on KFC Restaurants in Pontianak. Primary data was gathered using questionnaire basedon 150 respondents of KFC customers in Pontianakusing probability sampling technique.Model analysis used is path analysis which split into two tests. The result of the first test showed that brand image, product quality and service quality significantly influence the customer satisfaction and the result of the second test showed that customer satisfaction significantly influence the customer repurchase intention, meanwhile, service quality variable proved to be not significantly influence the customer repurchase intention. The result of direct and indirect influence testingwhich proves the total effect is greater than the direct effect is the influence of Brand Image, Product Quality and Service Quality toward Customer Repurchase Intention. This proves that Customer Satisfaction as a mediating variable is able to strengthen the independent and dependent variables.